Social dimensions of science–humanitarian collaboration: lessons from Padang, Sumatra, Indonesia. Issue 3 (July 2014) - Shannon, Rachel; Hope, Max; McCloskey, John; Crowley, Dominic; Crichton, Peter
<x xml:space="preserve">Abstract</x> This paper contains a critical exploration of the social dimensions of the science–humanitarian relationship. Drawing on literature on the social role of science and on the social dimensions of humanitarian practice, it analyses a science–humanitarian partnership for disaster risk reduction (DRR) in Padang, Sumatra, Indonesia, an area threatened by tsunamigenic earthquakes. The paper draws on findings from case study research that was conducted between 2010 and 2011. The case study illustrates the social processes that enabled and hindered collaboration between the two spheres, including the informal partnership of local people and scientists that led to the co‐production of earthquake and tsunami DRR and limited organisational capacity and support in relation to knowledge exchange. The paper reflects on the implications of these findings for science–humanitarian partnering in general, and it assesses the value of using a social dimensions approach to understand scientific and humanitarian dialogue.